Reporting of Drug-Related Crimes: Resident and Police Perspectives in the United States, 1988-1990 - Davis, Robert C. ([Verlag nicht ermittelbar], 1993)
This data collection investigates the ways in which police use reports of drug-related crimes provided by residents of high drug/crime areas and how willing residents of these areas are to report such crimes to the police. Structured interviews were conducted by telephone with police representatives in most of the nation's 50 largest cities and in person with residents and police officers in high drug/crime districts in each of four major cities: Newark, Chicago, El Paso, and Philadelphia. Police department representatives were queried about the usefulness of citizen reports, reasons for citizens' reluctance to make reports, how the rate of citizen reports could be improved, and how citizen reports worked with other community crime prevention strategies. Residents were asked about their tenure in the neighborhood, attitudes toward the quality of life in the neighborhood, major social problems facing the neighborhood, and quality of city services such as police and fire protection, garbage collection, and public health services. Additional questions were asked about the amount of crime in the neighborhood, the amount of drug use and drug-related crime, and the fear of crime. Basic demographic information such as sex, race, and language in which the interview was conducted is also provided.